(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Chemomechanical caries removal, though one of the most viable alternatives to conventional methods of caries removal, is still not much practiced due to the high treatment cost and extensive training required for its use, especially in developing countries. The present paper aims to highlight at a chemomechanical agent that is readily available and inexpensive, analyze its effectiveness as a chemomechanical agent and further discuss the alterations that can be made to use it as a chemomechanical agent commercially for the pediatric population.